A Case of Radiation-Induced Optic Neuropathy and Retinopathy after Radiation Therapy, Chemotherapy, and Immunotherapy for Brain Metastasis - Jimenez, Brittney; Tran, Angelina; Huang, Lisa; Segu, Bhagya (Canadian Journal of Optometry, 2023)
Radiation-induced optic neuropathy and retinopathy are associated with higher dose radiation therapy and can lead to devastating vision loss. This case report follows a 72-year-old Hispanic male with extensive stage IV small cell lung cancer and brain metastasis who presented with radiation-induced optic neuropathy and retinopathy. The patient’s cancer treatment included whole brain external radiation therapy, chemotherapy, immunotherapy, and thoracic radiation therapy prior to his eye examination. Consideration should be given to the size of individual fractions administered during radiation therapy in patients concomitantly undergoing chemotherapy and immunotherapy when managing radiation-induced ocular sequelae.